The use of magnetic susceptibility as a forensic search tool. (January 2015) - Pringle, Jamie K.; Giubertoni, Matteo; Cassidy, Nigel J.; Wisniewski, Kristopher D.; Hansen, James D.; Linford, Neil T.; Daniels, Rebecca M.
Graphical abstract: Highlights: Magnetic susceptibility an under-utilised forensic search tool. Relatively low cost, simple and quick to collect surface data. Variety of test studies show measurable contrast over target versus background. Use in active forensic case next stage. Abstract: There are various techniques available for forensic search teams to employ to successfully detect a buried object. Near-surface geophysical search methods have been dominated by ground penetrating radar but recently other techniques, such as electrical resistivity, have become more common. This paper discusses magnetic susceptibility as a simple surface search tool illustrated by various research studies. These suggest magnetic susceptibility to be a relatively low cost, quick and effective tool, compared to other geophysical methods, to determine disturbed ground above buried objects and burnt surface remains in a variety of soil types. Further research should collect datasets over objects of known burial ages for comparison purposes and used in forensic search cases to validate the technique.